Development and implementation of Solar-Thermoelectric Hybrid Energy Harvester - Anish Kumar; Praveen Kumar Choudhary (International Journal of Machine Systems and Manufacturing Technology, 2026)
In today’s consumer-oriented and technology-driven market, researchers are increasingly emphasizing the need to harvest energy from ambient and renewable sources to support sustainable power generation and to minimize dependence on conventional energy resources such as batteries and fossil-fuel-based electricity. The rising deployment of portable electronics, wireless sensor networks, and Internet of Things (IoT) devices has created an urgent demand for compact, low-power, long-life, and maintenance-free energy solutions. In many real-world scenarios, frequent battery replacement is impractical due to high cost, limited accessibility, and environmental concerns related to battery disposal. Hence, ambient energy harvesting has emerged as a promising approach for enabling self-powered electronic systems.Energy harvesting techniques provide enormous potential by converting naturally available energy such as human motion, mechanical vibrations, thermal gradients, airflow, and other waste energy into usable electrical output. Generally speaking, energy harvesters are transducers that take in energy from their surroundings and transform it into electrical power that may be stored or used directly.Among various harvesting mechanisms, triboelectric and thermoelectric energy harvesting methods are considered highly advantageous due to their simple structure, lightweight configuration, scalability, and suitability for small-scale applications
Keywords: DC-DC boost converter; STEG; TEG modules; generator system; thermocouple